Los nuevos modelos de gestión de las empresas mediáticas - Campos Freire, Francisco (Estudios sobre el Mensaje Periodístico, 2010)
The structural and situational crisis suffered by the Media in the past three years could have bottomed out in 2010 and started to recover through a profound industrial restructuring, innovation on business models, segmentation and optimisation of the different channels and market segments, digital convergence, development of new diffusion channels and content value engineering based on the strength, reputation and credibility of editorial companies. This study is based on direct observation of trends in the sector and quantitative and qualitative data from statistical surveys and financial results of the main industry players. The main sources of information used are: the worldwide association of newspapers (WAN), the IFRA professional association, diffusion and audiometric measurement, observed trends and market prospects.
Keywords: Media management; Business models; Integral organisation; Business networks; Editorial convergence; Innovation; Credibility and reputation